การวิเคราะห์รูปแบบค่าใช้จ่ายของครัวเรือนไทย ก่อนและหลังโครงการหลักประกันสุขภาพถ้วนหน้า - นันทศักดิ์ มะลิลา (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The objective of this study was to investigate the expenditure pattern of medical and healthcare services and the consumption pattern of Thai households before and after the universal health coverage scheme and the influence of socio-economic variables using Heckman selection model technique to find the factors that influence the expenditure pattern of medical and healthcare services. And using the ordinary least square (OLS) technique to measure the determinant factors of non-health consumption expenditure. Data used in this study were from Socio-Economic Survey (SES) in 2000 and 2009 by National Statistical Official. The quantitative results show that the characteristics of household such as the part of area that household situated, number of household member, municipality, household ownership, gender of head of the household, education level of head of the household, income of the household, and availability of universal health care for the household are important and statistically significant determination factor of the pattern of health expenditure. For example, household lived in Bangkok would have health expenditure significantly higher than other region. Moreover, if the head of household is covered by the universal health care coverage scheme, the health expenditure of that household would be higher compared with the household that the head is not covered by the universal health care coverage scheme at 99% significant level.